2009
DOI: 10.1073/pnas.0901840106
|View full text |Cite
|
Sign up to set email alerts
|

Optimal neuroprotection by erythropoietin requires elevated expression of its receptor in neurons

Abstract: Erythropoietin receptor (EpoR) binding mediates neuroprotection by endogenous Epo or by exogenous recombinant human (rh)Epo.The level of EpoR gene expression may determine tissue responsiveness to Epo. Thus, harnessing the neuroprotective power of Epo requires an understanding of the Epo-EpoR system and its regulation. We tested the hypothesis that neuronal expression of EpoR is required to achieve optimal neuroprotection by Epo. The ventral limbic region (VLR) in the rat brain was used because we determined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
77
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 41 publications
1
77
0
Order By: Relevance
“…As previously mentioned (Sanchez et al 2009), overexpression of Epo-R is necessary for a successful treatment with exogenously administered rHu-Epo. It was also demonstrated that MDR-1 gene overexpression could cause an impairment of brain hypoxia treatment with conventional drugs (Dohgu et al 2007;Xiao-Dong et al 2008).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…As previously mentioned (Sanchez et al 2009), overexpression of Epo-R is necessary for a successful treatment with exogenously administered rHu-Epo. It was also demonstrated that MDR-1 gene overexpression could cause an impairment of brain hypoxia treatment with conventional drugs (Dohgu et al 2007;Xiao-Dong et al 2008).…”
Section: Resultsmentioning
confidence: 93%
“…Interestingly, it was recently demonstrated that a single hypoxic exposure (1 h) has no effect on the Epo-R transcript basal levels in neurons immediately after hypoxia, but repetitive hypoxic stimulus can increase [85% the Epo-R transcript level (Sanchez et al 2009). In addition, animals exposed to an experimental model of sleep apnea by intermittent hypoxia showed a persistence of elevated HIF-1a in hippocampal neurons (Aviles-Reyes et al 2010).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Erythropoietin and its receptors are abundant in the developing brain and persist in the adult hypothalamus, hippocampus and neocortex. 25 Unlike BDNF, EPO crosses the blood-brain barrier 26 to impart neuroprotective effects, and EPO was found to have such actions in models of stroke and traumatic brain injury. 27 Indeed, EPO is already routinely used to help repopulate immune cells following chemotherapy and generally is considered to be well tolerated and safe, although careful titration of doses is essential given its ability to mobilize large numbers of red blood cells that could have negative vascular effects.…”
mentioning
confidence: 99%
“…30 Perhaps most importantly in regard to neuroplasticity and depression, EPO may increase BDNF expression and adult hippocampal neurogenesis 31 and hippocampal EPO levels were elevated after antidepressant or electroconvulsive shock treatments. 25,30 Thus, EPO could promote antidepressant effects by inducing BDNF expression or alternatively, by directly stimulating trophic pathways involving phosphatidylinositol-3-kinase (PI3-K), Akt/protein kinase-B, MAP kinases and STAT5. 32 It is also possible that EPO-induced BDNF could act synergistically with exogenously applied EPO to reinforce antidepressant-like actions, since both factors act through PI3-K and MAP kinase pathways.…”
mentioning
confidence: 99%